Growth Hormone Receptor Deletion Reduces the Density of Axonal Projections from Hypothalamic Arcuate Nucleus Neurons. (10th May 2020) - Wasinski, Frederick; Furigo, Isadora C.; Teixeira, Pryscila D.S.; Ramos-Lobo, Angela M.; Peroni, Cibele N.; Bartolini, Paolo; List, Edward O.; Kopchick, John J.; Donato, Jose
Highlights: Formation of POMC and AgRP projections requires GH and leptin signaling. POMC and AgRP projections are affected by LepR-specific GH receptor disruption. AgRP innervation is impaired in mice carrying AgRP-specific GH receptor ablation. Abstract: The arcuate nucleus (ARH) is an important hypothalamic area for the homeostatic control of feeding and other metabolic functions. In the ARH, proopiomelanocortin- (POMC) and agouti-related peptide (AgRP)-expressing neurons play a key role in the central regulation of metabolism. These neurons are influenced by circulating factors, such as leptin and growth hormone (GH). The objective of the present study was to determine whether a direct action of GH on ARH neurons regulates the density of POMC and AgRP axonal projections to major postsynaptic targets. We studied POMC and AgRP axonal projections to the hypothalamic paraventricular (PVH), lateral (LHA) and dorsomedial (DMH) nuclei in leptin receptor (LepR)-deficient mice ( Lepr db/db ), GH-deficient mice ( Ghrhr lit/lit ) and in mice carrying specific ablations of GH receptor (GHR) either in LepR- or AgRP-expressing cells. Lepr db/db mice presented reduction in the density of POMC innervation to the PVH compared to wild-type and Ghrhr lit/lit mice. Additionally, both Lepr db/db and Ghrhr lit/lit mice showed reduced AgRP fiber density in the PVH, LHA and DMH. LepR GHR knockout mice showed decreased density of POMC innervation in the PVH and DMH, compared to control mice, whereas a reduction in the density of AgRP innervation was observed in all areas analyzed. Conversely, AgRP-specific ablation of GHR led to a significant reduction in AgRP projections to the PVH, LHA and DMH, without affecting POMC innervation. Our findings indicate that GH has direct trophic effects on the formation of POMC and AgRP axonal projections and provide additional evidence that GH regulates hypothalamic neurocircuits controlling energy homeostasis.